Estimation of Naturally Produced Water-Soluble Vitamins in Different Asavas and Arishtas Using Liquid Chromatography - Singh, Nikhil Kumar; Sharma, Alok; Sharma, Meena; Singh, Rahul; Katiyar, Chandrakant (Fakultas Farmasi, Universitas Gadjah Mada, 2013)
Self fermented polyherbal Ayurvedic preparations are called Asavas and Arishtas and are efficacious classical preparations. Insignificant efforts have been made to delve deep into scientific rationale of this ancient dosage form of Ayurveda. An investigative analysis using reversed phase chromatography was conducted to evaluate and estimate the presence of water-soluble vitamins in seven Asavas and Arishtas namely Drakshasava, Ashokarishta, Dashmulrishta, Khadirarishta, Lauhasava, Arjunarishta and Ashwagandharishta. The study revealed that these preparations contained water soluble vitamins B1, B2, B3 & B6 in significant concentrations. Reversed phase high performance liquid chromatography was carried out on an Agilent 1200 DAD system. Separation was carried out on an Inertsil ODS 3 V column (250 mm x 4.6 mm, 5 Âµm) at wavelength of 265 nm.Â